A Combination of Chest Radiography and Estimated Plasma Volume May Predict In-Hospital Mortality in Acute Heart Failure - Kobayashi, Masatake; Douair, Amine; Coiro, Stefano; Giacomin, Gaetan; Bassand, Adrien; Jaeger, Déborah; Duarte, Kevin; Huttin, Olivier; Zannad, Faiez; Rossignol, Patrick; Chouihed, Tahar; Girerd, Nicolas (Frontiers in Cardiovascular Medicine, 2022)
Background Patients with heart failure (HF) often display dyspnea associated with pulmonary congestion, along with intravascular congestion, leading to urgent hospitalization and subsequent death. A combination of radiographic pulmonary congestion and plasma volume might screen patients with a high risk of in-hospital mortality in the emergency department (ED). Methods In the Pathway of dyspneic patients in Emergency (PARADISE) cohort, patients admitted for acute HF were stratified into 4 groups based on high or low congestion score index (CSI, ranging from 0 to 3, high value indicating severe congestion) and estimated plasma volume status (ePVS) calculated from hemoglobin/hematocrit. Results In a total of 252 patients (mean age, 81.9years; male, 46.8%), CSI and ePVS were not correlated (Spearman rho<0.10, p>0.10). High CSI/high ePVS was associated with poorer renal function, but clinical congestion markers (i.e., natriuretic peptide) were comparable across CSI/ePVS categories. High CSI/high ePVS was associated with a 4-fold higher risk of in-hospital mortality (adjusted-OR, 95%CI=4.20, 1.10-19.67) compared with low CSI/low ePVS, whereas neither high CSI nor ePVS alone was associated with poor prognosis (all-p-value>0.10; Pinteraction=0.03). High CSI/high ePVS improved a routine risk model (i.e., natriuretic peptide and lactate) (NRI=46.9%, p=0.02), resulting in high prediction of risk of in-hospital mortality (AUC=0.85, 0.82-0.89). Conclusion High CSI/high ePVS was associated with a high risk of in-hospital death, and improved prognostic performance on top of a conventional risk model. This readily and widely available congestion assessment, integrating chest radiography and hemoglobin/hematocrit, may be a better risk stratifier for acute heart failure patients in ED.